Iron‐Promoted CC Bond Formation in the Gas Phase. (8th October 2015) - Troiani, Anna; Rosi, Marzio; Garzoli, Stefania; Salvitti, Chiara; de Petris, Giulia
Abstract: An unusual iron transfer and carbon–carbon coupling take place in gas‐phase ionized mixtures containing ferrocene and dichloromethane. Ferrous chloride and the protonated benzenium ion are eventually formed by a thermal and efficient reaction, through stable intermediates that undergo a remarkable reorganization. The mechanism of the concerted iron extrusion, carbon–chlorine bond activation and carbon–carbon bond formation is elucidated by electronic structure calculations that show the crucial role of iron.